Comparison of embryo yield and pregnancy rate between in vivo and in vitro methods in the same Nelore (Bos indicus) donor cows - Pontes, J. H. F.; Nonato-Junior, I.; Sanches, B. V.; Ereno-Junior, J. C.; Uvo, S.; Barreiros, T. R. R.; Oliveira, J. A. [UNESP]; Hasler, J. F.; Seneda, M. M. (Elsevier B.V., 2009)
To investigate why the preferred means to produce bovine embryos in Brazil has changed from in vivo to in vitro, we compared these two approaches in the same Nelore cows (n = 30) and assessed total embryo production and pregnancy rates. Without a specific schedule, all cows were subjected to ultrasound-guided ovum pick up (OPU)/in vitro production (IVP) and MOET, with intervals ranging from 15 to 45 d between procedures, respectively. To produce in vivo embryos, cows were superovulated and embryos were recovered nonsurgically from 1 to 3 times (1.4 +/- 0.6). whereas OPU/IVP was repeated from 1 to 5 times (3.2 +/- 1.2) in each donor cow during a 12-mo interval. Embryos obtained from both methods were transferred to crossbred heifers. on average. 25.6 +/- 15.3 immature oocytes were collected per OPU attempt. The average number of embryos produced by OPU/IVP (9.4 +/- 5.3) was higher (P < 0.05) than the MOET method (6.7 +/- 3.7). However, pregnancy rates were lower (P < 0.05) following transfer of IVP (33.5%) versus in vivo-derived embryos (41.5%) embryos. Embryonic losses between Days 30 and 60 and fetal sex ratio were similar (P > 0.05) between in vivo and in vitro-derived embryos. We concluded that in Nelore cows, with an interval of 15 d between OPU procedures, it was possible to produce more embryos and pregnancies compared to conventional MOET. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: In vitro fertilization; Ovum pick up; Embryo transfer; Cattle; Nelore